Basic Methods of Cell Cycle Analysis - Ligasová, Anna; Frydrych, Ivo; Koberna, Karel (International journal of molecular sciences, 2023)
Cellular growth and the preparation of cells for division between two successive cell divisions is called the cell cycle. The cell cycle is divided into several phases; the length of these particular cell cycle phases is an important characteristic of cell life. The progression of cells through these phases is a highly orchestrated process governed by endogenous and exogenous factors. For the elucidation of the role of these factors, including pathological aspects, various methods have been developed. Among these methods, those focused on the analysis of the duration of distinct cell cycle phases play important role. The main aim of this review is to guide the readers through the basic methods of the determination of cell cycle phases and estimation of their length, with a focus on the effectiveness and reproducibility of the described methods.
Keywords: Cell Cycle; proliferace buněk; buněčné dělení; Reproducibility of Results; DNA labeling; EdU; time lapse microscopy; bromodeoxyuridin; Bromodeoxyuridine; BrdU; Cell Division; Cell Proliferation; reprodukovatelnost výsledků; labeled nucleosides; markers of cell cycle phases; cell cycle; buněčný cyklus